Implementation of Character Education In Fostering Elementary School Students In Gelumbang, Indonesia - Yuhanis Yuhanis; Yasir Arafat; Artanti Puspitasari (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
This paper is a qualitative research, which aimed at providing an overview of the implementation of character education in fostering students at SD Negeri 17 Gelumbang. The subjects in this study were the principal, teachers, and students. Data collection were carried out through interviews, observation and documentation. Data were analyzed by reduction, presentation, and conculsion. The results concluded that the implementation of character values ​​at SD Negeri 17 Gelumbang is carried out by internalizing character values ​​into compulsory subject matter, namely Islamic Religious Education, Citizenship Education, Indonesian Language, Mathematics, Social Sciences, Natural Sciences, and Physical Health Education through a learning process. The implementation of character values ​​at SD Negeri 17 Gelumbang is carried out programmatically.